Objective-Based Exegesis Of The Qur'an: A Conceptual Framework - Tazul Islam; Amina Khatun (Centre of Quranic Research (CQR), University Malaya, 2024)
Al-Tafsir al-Maqasidi represents an exclusive maqasidic (purposive) trend in Qur’anic exegesis. In the available trends in tafsir, the maqasidic approach has yet to be treated exclusively and has been subject to only partial discussions. For the sake of a better understanding, a transformation in this trend from being inclusive to exclusive is needed. Unlike other exegetical trends in terms of basic components, mechanisms and focus, al-Tafsir al-Maqasidi centres on exploring the objectives of the Qur’an in a methodological manner.It then outlines how the Qur’anic contents develop a purposive (maqasidic) unity based on objectives and their means.Subsequently, it explores how these objectives materialised in the first generation of Islam. Thus, an exegesis in the light of these basic components would usher new angles, dimensions and methods of understanding the particular aspects of the Qur’an.